Perlindungan Hukum Tentang Pengembangan Pelabuhan Di Daerah Sesuai Undang-Undang tentang Pelayaran Kaitannya dengan Undang-Undang tentang Pemerintahan Daerah - Sitompul, Patartua H.; Nasution, Mirza; Harianto, Dedi; Mubarak, Ridho (ARBITER: Jurnal Ilmiah Magister Hukum, 2020)
The problems in this research are: First, how is legal protection, legal compliance and overcoming problems regarding the management of ports in the regions according to Law Number 23 of 2014 concerning Regional Government and its relation to Law Number 17 of 2008 concerning Shipping. The method used in this research is normative legal research, namely research that refers to legal norms and principles contained in statutory regulations and government regulations. The result of the research is that Law Number 17 of 2008 concerning Shipping contains articles that regulate ports which require further regulation in the form of a Government Regulation. The law establishes a system of port authority that will carry out a regulatory role, end state-owned monopoly control over port services, and require the development of national and regional port master plans. Legal protection in implementing regional autonomy is in accordance with the enactment of Law Number 23 of 2014 concerning Regional Government, legal protection for the implementation of various government affairs in the framework of serving the community and managing natural resources. The problems that have arisen in the management of ports in the regions so far are conflicts of use and power. It is hoped that the efforts to deal with these problems can be carried out reactively, meaning that local governments can carry out conflict resolution, mediation or deliberation in dealing with these problems.